Living in fear at the unpredictability of mental health issues in the classroom: a phenomenological study of secondary school teachers in encountering students with mental health issues - Liang, Mining; Ho, Grace W. K.; Christensen, Martin (Frontiers in Psychiatry, 2024)
The prevalence of mental health issues among secondary school students is on the rise. Secondary school teachers, outside the home environment, are often in a prime position to identify adolescents facing mental health challenges. Limited knowledge regarding the experiences and perspectives of secondary school teachers when encountering this particular group of students, particularly in Asian countries.Objectives: This study aimed to describe the lived experiences of secondary school teachers exposed to students with mental health issues in the classroom in a Chinese context.A descriptive phenomenological approach within the tradition of Husserl was used. A purposive sampling method was used to collect the participants in Changsha, Hunan, China.Sixteen secondary school teachers participated in this study. Individual, face-to-face interviews were conducted, tape-recorded, and transcripted. Colaizzi's seven-step descriptive phenomenological method was used to do the data analysis.: One Central theme: Living in fear at the unpredictability of mental health issues in the classroom and four sub-themes emerged: (1) Worried and anxious by the uncertainty of student mental health issues; (2) Scared and afraid by students' unpredictable behaviors; (3) Afraid of students' failure and its potential outcome; (4) Students having mental health issues are dangerous.The teachers in this study found managing the unpredictability of mental health issues in the classroom deeply distressing and challenging. A comprehensive approach to address the cultural, social, and educational factors influencing secondary school teachers' experiences is encouraged.